2006
DOI: 10.1198/016214506000000168
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Racial Profiling in Traffic Stops From Behind a Veil of Darkness

Abstract: The key problem in testing for racial profiling in traffic stops is estimating the risk set, or "benchmark," against which to compare the race distribution of stopped drivers. To date, the two most common approaches have been to use residential population data or to conduct traffic surveys in which observers tally the race distribution of drivers at a certain location. It is widely recognized that residential population data provide poor estimates of the population at risk of a traffic stop; at the same time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
176
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 14 publications
1
176
0
Order By: Relevance
“…Our inability to estimate this fully specified model is not surprising since, even if c is a constant, there are only four possible cases of driver / officer interactions but five parameters. 12 If blacks and whites are not equally prejudiced, then our estimates will uncover the average level of prejudice across black and white officers. 13 In order to derive these relationships, consider the following four possible cases of driver/officer interactions for both the theoretical and empirical models: 1) j = w, r = w, 2) j = a, r = a,3) j = w, r = a,4) j = a, r = w. One can then show that β 0 + β 1 c = π(c, w) + t w w .…”
Section: Racial Prejudicementioning
confidence: 98%
“…Our inability to estimate this fully specified model is not surprising since, even if c is a constant, there are only four possible cases of driver / officer interactions but five parameters. 12 If blacks and whites are not equally prejudiced, then our estimates will uncover the average level of prejudice across black and white officers. 13 In order to derive these relationships, consider the following four possible cases of driver/officer interactions for both the theoretical and empirical models: 1) j = w, r = w, 2) j = a, r = a,3) j = w, r = a,4) j = a, r = w. One can then show that β 0 + β 1 c = π(c, w) + t w w .…”
Section: Racial Prejudicementioning
confidence: 98%
“…Studies in Portland and Cincinnati found no reduction in disparity at night, concluding that disparities were not caused by racial discrimination. 189 Studies in Minneapolis and Syracuse reached the opposite conclusion; the Syracuse study, unlike the others, accounted for variations in artificial light. 190 These studies are very clever.…”
Section: Exploiting Variations In Enforcers" Information About Racementioning
confidence: 83%
“…This confirms that less information (no criminal background check) leads to resorting to race as a proxy of productivity. The impact of race-specific speech patterns, collected from recorded interviews, on the employer's understanding of speaker characteristics has also been evaluated by Grogger (2011) through OSL and median regressions. He found that speakers identified as black earned about 17% less than whites, after controlling for personal and ability characteristics.…”
Section: Annotated Bibliographymentioning
confidence: 99%